Knowledge on occupational health and safety among healthcare workers in Penampang, Putatan and Inanam Health Clinics Sabah - Shamsul Kamal, bin Abd. Latip @ Mohd (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The objective of this study was to determine the level of knowledge on general OHS, OHS legislation, occupational hazards and PPE among healthcare workers in Penampang, Putatan and Inanam Health Clinics, Sabah. A cross sectional study was administered to a sample of healthcare workers in the 3 health clinics. The healthcare workers were divided into 3 main groups; professional, supporting medical and supporting non medical. The healthcare workers were also divided into 2 groups Gunior and senior) based on their length of service. An I8-item self administered questionnaire was used. The questionnaire covered the 4 topics stated in the objective. Level of knowledge was categorized into good (2::75%) and fair « 75o/oJ The response rate was 88.8% (182 respondents). Overall level of knowledge on occupational health and safety was fair, with a mean score of -67.8%. The respondents were more knowledgeable about PPE, with a mean score of 95.2% and less knowledgeable about OHS legislation with a mean score of 59.3%. Their mean score for occupational hazards and general OHS knowledge were 68.6% and 62.3% respectively. Results also showed that more healthcare workers from professional group had good knowledge on occupational health and safety (43.5%) and length of service had no effect on the level of knowledge on occupational health and safetyof the healthcare workers. Conclusion from this study is that the OHU, Sabah State Health Department together with Kota Kinabalu and Penampang Area Health Office need to make more efforts to promote and increase the knowledge on occupational health and safety among the healthcare workers in the 3 health clinics.